2019
DOI: 10.1039/c8py01618f
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced water transport in AEMs based on poly(styrene–ethylene–butylene–styrene) triblock copolymer for high fuel cell performance

Abstract: Anion exchange membrane fuel cells (AEMFCs) have received a considerable amount of attention in the past decades as a lower cost alternative to proton exchange membrane fuel cells (PEMFCs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 51 publications
0
36
0
Order By: Relevance
“… 8 , 34 This severely limits the stability and usefulness of AEM-carrying BTMA cations and typically restricts the AEMFC operating conditions. Two unrelated studies on SEBS functionalized with BTMA reported 19 32 and 28% 33 reductions in IEC, respectively, after 71 and 31 days, respectively, in 1 M aq KOH at 60 °C. Separation of the cation from the benzylic position has proven beneficial both in studies of model compounds 8 , 9 and in AEMs.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“… 8 , 34 This severely limits the stability and usefulness of AEM-carrying BTMA cations and typically restricts the AEMFC operating conditions. Two unrelated studies on SEBS functionalized with BTMA reported 19 32 and 28% 33 reductions in IEC, respectively, after 71 and 31 days, respectively, in 1 M aq KOH at 60 °C. Separation of the cation from the benzylic position has proven beneficial both in studies of model compounds 8 , 9 and in AEMs.…”
Section: Introductionmentioning
confidence: 98%
“… 21 24 Polystyrene (PS) is another example of an ether-free polymer that has been extensively investigated for the preparation of AEMs in the form of block and graft copolymers. 25 33 Varcoe et al have investigated the radiation grafting of poly(vinylbenzyl chloride) onto thin films of ethylene-tetrafluoroethylene (ETFE) 26 , 27 and low-density polyethylene (LDPE), 28 followed by quaternization with trimethylamine. Recently, fuel cell tests of such AEMs achieved >2 W cm –2 , which is one of the highest power densities reported for an AEMFC to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Raising their IEC is an efficient and simple way to improve the conductivity of AEMs. Unfortunately, membrane swelling is generally accompanied with high IEC and thus results in poor mechanical strength of AEMs (Pan et al, 2012;Lu et al, 2013;Hou et al, 2016;Shukala and Shahi, 2018;Gao et al, 2019a). The swelling ratio of AEMs could be greatly reduced by introducing cross-linked structures, while the tight structure of membranes hinder the mobility of OH − , which reduces their conductivity (Liang et al, 2019;Lin et al, 2019b).…”
Section: Hydroxide Conductivitymentioning
confidence: 99%
“…Diffusion resistance of AEMs can also be tuned by controlling the hydrophilicity of the AEMs. X. Gao, et al characterized water transport properties of poly (styrene-ethylene-butylene-styrene) based AEM as function of temperature and RH[137]. It was found that the water permeation flux through the AEM increased with temperature following the Fick's law of diffusion and was proportional to the water content gradient and diffusion coefficient.…”
mentioning
confidence: 99%